Implants for surgery - active implantable medical devices - part 1: general requirements for safety, marking and for information to be provided by the manufacturer (ISO 14708-1:2000, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Raj, Caroline; T, Mahadevan; Wong, Darren; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Yusof, Shahril; Manickam, Thirumal; Mohd Yusof, Hyzan; et al. (SIRIM, 2010)
This Malaysian Standard specifies requirements that are generally applicable to active implantable medical devices. This standard is applicable not only to active implantable medical devices that are electrically powered, but also to those powered by other energy sources (for example gas pressure or springs). This standard is also applicable to some non-implantable parts and accessories of the devices.